Mitigasi Risiko Keamanan Data dalam Implementasi Sertifikat Tanah Elektronik untuk Mewujudkan Kepastian Hukum bagi Pemegang Hak Atas Tanah - Ach Farhan Arif; Herowati Poesoko; Miftahul Munir (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2025)
Digital transformation in land services has introduced the innovation of electronic land certificates, replacing the conventional physical system of analog certificates. This initiative by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (BPN) is expected to enhance administrative efficiency in land services, accelerate service processes, and provide legal certainty for landowners. However, the implementation of electronic land certificates also presents challenges related to land data security and legal protection. Risks such as data manipulation, cyberattacks, and data loss are key issues that could hinder the sustainability of this system. This research aims to identify risk mitigation strategies necessary to ensure legal certainty for landowners. Using a normative juridical research type with a perspective analysis approach, the study highlights the importance of adequate regulatory harmonization and advanced technology in managing land data security.The research findings indicate that effective risk mitigation requires collaboration between the government—particularly the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (BPN) at central and regional levels—and other stakeholders related to legal protection of electronic documents. Through holistic mitigation strategies, electronic land certificates can not only enhance efficiency but also provide optimal legal protection needed to build public trust in the digital land system. Consequently, the sustainability of the digital system through electronic land certificates can be achieved. This research provides recommendations to strengthen data security systems, improve regulations, and educate the public as crucial steps in transforming land services